PENGARUH KEBIJAKAN DIVIDEN, KEPEMILIKAN MANAJERIAL DAN UKURAN PERUSAHAAN TERHADAP TINDAKAN PERATAAN LABA - Saidah, Zidni; Hariyono, Anwar (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2023)
The aim of this research is to provide empirical evidence on the influence of dividend policy, managerial ownership and company size on income smoothing actions. The population of this research includes all manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Purposive sampling technique was used to select samples according to the criteria set by the researcher, so that a sample of 22 companies was obtained with 3 years of observation. This research uses logistic regression analysis because the dependent variable in this research is a dummy variable. The research results show that dividend policy has no influence on income smoothing actions. Meanwhile, managerial ownership and company size have a significant positive influence on income smoothing. So the first hypothesis is rejected while the second and third hypotheses are accepted.